Life Cycle Sustainability Analysis of Resource Recovery from Waste Management Systems in the Context of Circular Models of the Economy and the Bioeconomy (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue aims to address the concern that sustainable waste management, from the perspective of the Circular Economy (CE), can contribute to a just and sustainable post-fossil carbon society. The time has come for CE-based societies where responsible and sustainable ways of dealing with waste are implemented and pursued. A successful transition will require the planning, design, testing, and implementation of waste-based products that satisfy the three dimensions of sustainability or the 17 UN Sustainable Development Objectives. This Special Issue further contributes to the awareness that waste can be valorised as a zero-burden resource and sustainably transformed into value-added material and energy commodities. It has also allowed us to understand that CE principles can be applied to a wide range of sectors and issues and that there are several scientific-based methodologies, such as LCA and others. These methodologies were confirmed by the articles in this Special Issue to be highly effective in scientifically assessing the impacts of CE measures on the systems to which they are applied. Finally, this Special Issue confirmed the importance of academic research for assessing and stimulating the integrated sustainability of waste recovery systems from the perspective of the CE. In this way, this Special Issue may serve as a platform for advancing knowledge on new methodologies, practical applications, state-of-the-art analysis, findings, and lessons learned in such an important and current research field.